New York Times Economic Security Poll, December 1996 ([Verlag nicht ermittelbar], 2007)
This poll, fielded December 8-11, 1996, is part of a continuing series of monthly surveys that solicit public opinion on the current presidency and on a range of other political and social issues. Respondents were asked to give their opinions of President Bill Clinton and his handling of the presidency and the economy. Respondents also were queried on what they thought was the most important problem the country faced and if things were going in the right or wrong direction. Many of questions dealt with issues pertaining to jobs including whether the respondent was currently employed, how worried the respondent felt that they or someone in their household could be out of work and looking for a job within the next 12 months, their job satisfaction, whether they were working an extra job, and if they had been forced to work reduced hours or take a pay cut. Respondents also were asked detailed questions concerning job layoffs including if they had been laid off in the last five years, from how many different jobs they had been laid off, if anyone else in the household had experienced a layoff, and if the respondent knew someone who had been laid off in the last 15 years. The respondents also were asked questions relating to new jobs that they had taken because of being laid off and whether they felt that layoffs and job loss were a temporary problem or if it would be a permanent problem in the United States. They were then asked whether the government should step in to do something about job loss, and if either the Republican party or Democratic party would be better suited to stop layoffs and loss of jobs. Many questions also dealt with the respondents' financial situation. They were asked if they had a savings account, shares in the stock market, or retirement savings and what their plans were for holiday spending. Demographic variables include sex, age, race, education level, household income, employment status, voter registration status, political ideology, party affiliation, marital status, number of children in the household, and whether respondents had a child who had entered the 9th grade starting in September 1996